2003
DOI: 10.1038/sj.bjc.6600926
|View full text |Cite
|
Sign up to set email alerts
|

Tumour dose response to the antivascular agent ZD6126 assessed by magnetic resonance imaging

Abstract: ZD6126 is a vascular targeting agent that disrupts the tubulin cytoskeleton of proliferating neo-endothelial cells. This leads to the selective destruction and congestion of tumour blood vessels in experimental tumours, resulting in extensive haemorrhagic necrosis. In this study, the dose-dependent activity of ZD6126 in rat GH3 prolactinomas and murine RIF-1 fibrosarcomas was assessed using two magnetic resonance imaging (MRI) methods. Dynamic contrast-enhanced (DCE) MRI, quantified by an initial area under th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
72
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(75 citation statements)
references
References 17 publications
2
72
0
1
Order By: Relevance
“…The dose-dependent changes measured in the murine and human tumors are consistent with the results of a study of ZD6126 in a rat prolactinoma model (25) and the preliminary findings from a Phase I trial for CA4P (23). In contrast, there was no evidence of a dose response reduction in tumor IAUC after the administration of DMXAA to patients (24).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The dose-dependent changes measured in the murine and human tumors are consistent with the results of a study of ZD6126 in a rat prolactinoma model (25) and the preliminary findings from a Phase I trial for CA4P (23). In contrast, there was no evidence of a dose response reduction in tumor IAUC after the administration of DMXAA to patients (24).…”
Section: Discussionsupporting
confidence: 76%
“…The results reported here show the potential of using DCE-MRI in ZD6126 dose-finding studies in humans. Although a number of studies have already shown the potential of using DCE-MRI with the vascular-targeting agents CA4P (7,(13)(14)(15)(21)(22)(23) and DMXAA (22,24), there is only one published study for ZD6126 (25). In addition, we have shown that ZD6126 dosedependent changes can be measured using MRI and that the approach developed in murine tumors can be translated into the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…DCE-MRI measurements showed that after just 2 days patupilone significantly decreased the rBVol (P = 0.0005). Other vascular variables, such as vessel permeability and overall perfusion, were unaffected, a distinct difference in vascular response in comparison with therapies that target vascular endothelial growth factor (24,37) or the vascular endothelial growth factor receptor (33) or the endothelial cells directly (38,39) and not necessarily expected given that other antivascular/disruptive therapies can decrease permeability and/or perfusion (9,40). Vascular casts of tumors made 2 days after treatment showed a trend for patupilone to induce a decrease in blood vessel mass, and at this time point, the tumor IFP was also decreased (P = 0.02).…”
Section: Discussionmentioning
confidence: 99%
“…DCE MRI was included as part of the Phase I clinical trials of CA4P (24,25). Results of preclinical and clinical DCE MRI studies have shown a reversible change in vascular perfusion in the tumor periphery following a single dose of VTA (26)(27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%